2017
DOI: 10.1097/pai.0000000000000340
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β and CTGF are Mitogenic Output Mediators of Wnt/β-Catenin Signaling in Desmoid Fibromatosis

Abstract: Desmoid fibromatosis is a locally aggressive clonal fibroblastic proliferation with high recurrence rates and no metastatic potential. Implicated molecular aberrations occur within the Wnt/β-catenin pathway (APC and β-catenin gene mutations). Transforming growth factor-β (TGF-β) and connective tissue growth factor (CTGF) are profibrotic growth factors, downstream from nuclear translocation of β-catenin, that lead to increased fibrogenesis. CTGF (a downstream effector of TGF-β) is a matricellular protein that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…30 THBS4 is an important pro-angiogenic factor that contributes to tumor growth via TGF-β pathway activation, which mediates Wnt/β-Catenin signaling in DT. 31,32 This study has limitations. It was a non-comparative randomized trial, therefore precluding direct comparison of the chemotherapy regimen with pazopanib.…”
Section: Discussionmentioning
confidence: 95%
“…30 THBS4 is an important pro-angiogenic factor that contributes to tumor growth via TGF-β pathway activation, which mediates Wnt/β-Catenin signaling in DT. 31,32 This study has limitations. It was a non-comparative randomized trial, therefore precluding direct comparison of the chemotherapy regimen with pazopanib.…”
Section: Discussionmentioning
confidence: 95%
“…β-Catenin primarily coordinates cell proliferation, differentiation and fate, with its deregulated signalling being intrinsically linked to the development of several human cancers, such as skin, colon and breast cancer [ 13 , 14 ]. β-Catenin demonstrated aberrant nuclear immunoreactivity in at least 47% of DTF cases [ 24 33 ]. DTF cases with a mutated CTNNB1 gene also demonstrated more frequent β-catenin nuclear expression (39/43, 90.7%) compared with cases with wild-type CTNNB1 (Fisher’s exact test, 17/27, 63.0%, p = 0.012) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies examined TFGβ signalling. Varghese et al illustrated moderate-strong TGFβ and connective tissue growth factor (CTGF) immunoreactivity in 100% and 66.7% of DTF cases, respectively [ 33 ]. Mignemi et al demonstrated phosphorylated SMAD2/3 immunoreactivity in 96% of their DTF cohort, which was significantly greater than both hypertrophic scar and normal fibrous tissue (Kruskal–Wallis test, p < 0.0001; Dunn’s post-hoc test, p < 0.001) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…myofibroblasts to encode fibrillary collagen (Dobaczewski et al, 2011) and participate in the transition from stable hypertrophy to heart failure (Lim and Zhu, 2006). Meanwhile, it was also found that CTGF, as a downstream mediator of TGFβ 1, also has a great effect on fibroblasts induced by TGFβ 1 (Varghese et al, 2017) and significantly upregulated in human heart failure and the myocardial fibrosis-associated animal model (Koshman et al, 2013). In addition, TNF-α, as a proinflammatory cytokine, promotes collagen deposition in fibrotic myocardium myocardia and ECM accumulation by affecting MMP expression and activity, which can lead to myocardial fibrosis (Leask, 2015).…”
Section: Discussionmentioning
confidence: 99%